Virtual and Remote Control Tower Research, Design, Development and Validation - Fürstenau, Norbert (Research Topics in Aerospace,, 2016)
The interdisciplinary research and development work carried out in the last ten years which is presented in this book aimed at replacing the conventional airport control tower by a new "remote tower operation" work environment (RTO) which should enhance work efficiency and safety and reduce costs. This revolutionary human-system interface allows for remote aerodrome traffic control without a physical tower building and enables the establishment of remote airport traffic control centers (RTC) of which each may serve several airports from a central location.